Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 81. Beitrag. Lepidoptera: Phycitidae I (Phycitinae). - Roesler, Rolf-Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 1969)
This paper is based almost exclusively on material collected by the expedition to Albania by Deutsches Entomologisches Institut in 1961; only a few individuals collected in Albania by Dr. Friese in 1959 are included. An evaluation of previous publications is not possible in this group without an examination of the specimens; consequently, earlier finds are not considered and no statements are made about new first finds in Albania which will certainly result from this collection. The present material consists of 201 individuals of 31 species, 2 subspecies and 3 forms. One genus (Michaeliodes gen. nov.), one species (Michaeliodes friesei spec. nov.) and one form (Eurhodope monogrammos Zeller f. melanella f. nov.) are newly described.Nomenclatural Actsaffusella Ragonot, 1888 (Ephestia), syn. n. of Ephestia elutella (Hübner, 1796)lutisignella Mann, 1862 (Euzopherodes), comb. nov.gianelliella Ragonot, 1887 (Hypochalcia), syn. n. of Hypochalcia athenella (Denis & Schiffermüller, 1775)friesei Roesler, 1969 (Michaeliodes), spec. n.Michaeliodes Roesler, 1969 (Phycitidae), gen. n.